ANALISIS PENGELOLAAN REKLAME OLEH DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) KABUPATEN TEGAL DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH TAHUN ANGGARAN 2010-2014 - Dwi Islami Estri Anggani; Warsito .; Turtiantoro . (Journal of Politic and Government Studies, 2016)
The objective of this study is to analyze advertisement management which is implemented by Department ofRevenue and Financial Management of The Local Asset (DPPKAD) Tegal Regency. Advertisement management is one of efforts to increase Regional Original Revenue in order to implement the government and reginal building. Therefore, this studywasanalyzing the organizing phases and what factors are being impeller and obstacle in this advertisement organizing process by using management function theory from George Terry which loads planning indicator, organization, actuating, and controlling.The method of data analysis was descriptive qualitative research. In collecting data, the study used observation technique, interview, documentation and literary studies. The study also used secondary data which came from documentation data and other literary sources such as books and reports or DPPKAD Tegal Regency’s archives.This study showed that advertisement management in Tegal Regency had been appropriate with the procedure but the implementation was not optimum yet, whether in planning phase, organization, actuating, or controlling. Some obstacles was still experienced by DPPKAD whether external obstacles such as less awareness from society to pay tax, or internal obstacles such as less effetiveness of employee’s performance. Therefore, the recommended suggestions from the researcher are optimization of advertisement managemnet which was done by increasing employee of DPPKAD’s performance and reducing or ommiting obstacles which along the period became obstacles in advertisement management in order to get advertisement tax income maximumly.